A valid and practical electronic digital security module for educational technology study program students - Ramadani, Putri; Anwar, Citra Rosalyn (Univeritas Papua, 2025)
This research is a development research (R&D) using the Rowntree model, which aims to produce digital safety e-modules for digital literacy study program students of FIP UNM. Educational Technology Study Program. The research method used is the research and development method using the Rowntree model. Data collection techniques include questionnaires, observations, assessment questionnaires, and documentation. Data analysis techniques used qualitative descriptive analysis techniques and quantitative descriptive analysis. The results of expert validation show that the Digital Safety e-Module that has been developed has obtained valid criteria with a percentage of 100% in the content aspect, a rate of 100% in the language aspect, and a percentage of 98% in the media design aspect. The practicality test of the product is seen from the average score of the questionnaire at the one-to-one evaluation stage and the field trial stage. The average assessment score was 95% at the one-to-one evaluation stage, with a very practical category. The average assessment score at the field trial stage was 92.5%, with a very practical category. Thus, the Digital Safety e-Module product for Digital Literacy Study Program Students, Department of Educational Technology FIP UNM, has been developed with validity and practicality.